Homogeneous Risk Measures and the Construction of Composite Assets - Breen, William (Journal of Financial and Quantitative Analysis, 1968)
The use of the expected utility hypothesis and the “portfolio approach” has recently become quite popular by both writers in monetary theory and in financial management. Most discussions are given within what might be called the Tobin-Markowitz framework. One very important result recently discussed at some length is the Tobin “separation theorem.” This theorem essentially says that a quadratic preference function, or a normal distribution of returns on risky assets is a sufficient condition for the proportions of the various risky assets in a portfolio to be independent of the proportion of the portfolio held in a safe asset. The proofs of this theorem are given within a framework of the decision maker who minimizes portfolio variance for a given portfolio return, using variance as a measure of risk of the portfolio.